2021
DOI: 10.3389/fpsyt.2021.682041
|View full text |Cite
|
Sign up to set email alerts
|

Collective Trauma and Mental Health in Adolescents: A Retrospective Cohort Study of the Effects of Retraumatization

Abstract: In the wake of the massive Canadian wildfire of May 2016 in the area of Fort McMurray Alberta, we observed increased rates of mental health problems, particularly post-traumatic stress disorder (PTSD), in school-aged adolescents (ages 11–19). Surprisingly, we did not see these rates decline over the 3.5-year follow-up period. Additionally, our research suggested that the impact of this mass incident resulted in other unanticipated effects, including the finding that children who were not present for and relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Between this study and our previous publication on the Fort McMurray wildfire ( 20 ), we show evidence of both sensitization and inoculation effects in the same subjects. Taken together, these papers contribute to the literature by demonstrating that both processes are likely at work at the same time.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Between this study and our previous publication on the Fort McMurray wildfire ( 20 ), we show evidence of both sensitization and inoculation effects in the same subjects. Taken together, these papers contribute to the literature by demonstrating that both processes are likely at work at the same time.…”
Section: Discussionsupporting
confidence: 82%
“…As has been reported previously ( 20 ), individuals with a previous history of trauma were significantly more likely to be older, male, and – not surprisingly – been exposed to less wildfire trauma. A detailed breakdown of all of the sample characteristics of the two groups, as well as the overall sample, are presented in Table 1 .…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…In comparison to the participants that completed their treatment round(s) prior to the onset of the pandemic, children and adolescents that began treatment after the onset of the pandemic consistently reported lower levels of improvement. Collective traumas, such as natural disasters or pandemics, have the capacity to retraumatize already vulnerable populations ( Pazderka et al, 2021 ), and may explain some of the differences in treatment outcomes observed. Social distancing, lockdowns, school closures, and a public health crisis has the potential to increase individual stress levels ( Ghosh et al, 2020 ; Wang et al, 2020 ) which could result in treatment resistance.…”
Section: Discussionmentioning
confidence: 99%